The maritime landscape of the Isthmus of Panamá - Delgado, James P. (University Press of Florida, 2017)
In its 11,000 year human history, the Isthmus of Panama has been dominated by its relationship to the sea and the rivers that feed it. A unique marine environment, the land bridge shaped its inhabitants' activities, and those inhabitants shaped the Isthmus - from harvesting resources to physically transforming the land to link two oceans. This seminal work explores this intersection between people and the environment, mining the archaeological and ethnological record created during the formation and development of Panama's maritime cultural landscape. Assessing sites both submerged and on land, the authors explore the maritime history of the isthmus through its many stages.